Comparative cell cycle transcriptomics reveals synchronization of developmental transcription factor networks in cancer cells - Boström, Johan; Sramkova, Zuzana; Salašová, Alena; Johard, Helena; Mahdessian, Diana; Fedr, Radek; Marks, Carolyn; Medalová, Jiřina; Souček, Karel; Lundberg, Emma; Linnarsson, Sten; Bryja, Vítězslav; et al. (PloS one, 2017)
The cell cycle coordinates core functions such as replication and cell division. However, cell-cycle-regulated transcription in the control of non-core functions, such as cell identity maintenance through specific transcription factors (TFs) and signalling pathways remains unclear. Here, we provide a resource consisting of mapped transcriptomes in unsynchronized HeLa and U2OS cancer cells sorted for cell cycle phase by Fucci reporter expression. We developed a novel algorithm for data analysis that enables efficient visualization and data comparisons and identified cell cycle synchronization of Notch signalling and TFs associated with development. Furthermore, the cell cycle synchronizes with the circadian clock, providing a possible link between developmental transcriptional networks and the cell cycle. In conclusion we find that cell cycle synchronized transcriptional patterns are temporally compartmentalized and more complex than previously anticipated, involving genes, which control cell identity and development.
Keywords: Neoplasms; transkripční faktory; Cell Cycle; nádorové buněčné linie; proteiny buněčného cyklu; algoritmy; Humans; Cell Line, Tumor; Cell Cycle Proteins; Algorithms; Transcription Factors; nádory; Transcriptome; lidé; buněčný cyklus; transkriptom